(untitled) (FULafia Journal of Science and Technology, 2018)
One of the major challenges in “poultry keeping” is how to diagnose, treat and manage different types of poultry diseases in the farm. Animal farmers and various poultry keepers run their businesses at loss especially when there is outbreak of poultry diseases which claims the life of millions of poultry birds. Unfortunately, enough efforts have not been made in terms of research, using Artificial Intelligence (AI) approach to solve or minimize this problem. This research work therefore made an attempt to develop an expert system to diagnose, treat and manage poultry diseases. In this research work, knowledge of experts - animal scientist, veterinary doctors and poultry keepers were used to develop a knowledge base for the system. Also, an inference engine was developed to relate with the knowledge base and the working memory. The system was implemented using C sharp (C#), and CLIP. The knowledge was finally made available to the users. The system was highly simplified and made user friendly. In fact, it was adjudged by the users to be better than the existing ones. Hence, the findings of this research will significantly help in reducing poultry mortality rate and thereby make poultry farming a viable business. This, in turn will encourage young school leavers to engage in poultry farming.